Konsekuensi Hukum bagi Debt Collector yang Melampaui Kewenangan: Studi Kasus PT Mega Central Finance Bagan Batu - Anggrayni, Dea; Sriono, Sriono; Siahaan, Nimrot (CV. Social Politic Genius (SIGn), 2024)
This study aims to analyze the authority of debt collectors from a civil law perspective, focusing on a case study of PT Mega Central Finance Bagan Batu. To achieve this objective, this study employs a mixed method of field research and normative legal research, where the collected data is analyzed qualitatively to describe the problems and answer the research objectives. The results show that the problem of bad credit encourages financing companies to use debt collectors’ services to optimize the collection process. Meanwhile, debt collectors must have competency certification and act based on an extraordinary power of attorney from the financing company, as regulated in Financial Services Authority Regulation Number 35/POJK.05/2018 and Article 1795 of the Civil Code. Despite having compiled a standard operating procedure for collection, PT Mega Central Finance Bagan Batu still encounters deviant debt collector practices that harm debtors, such as intimidation, threats, and seizure of collateral without legal procedures. These actions violate the rights of debtors and legal principles. The legal consequences and implications cover criminal law, civil law, consumer protection law, and administrative sanctions from the Financial Services Authority.